Madame Léon Clapisson from Renoir Paintings and Drawings at the Art Institute of Chicago - Groom, Gloria (Art Institute of Chicago, 2014)
This portrait of Madame Léon Clapisson is one of twenty-five works that are featured in Renoir Paintings and Drawings at the Art Institute of Chicago. This catalogue features new art historical research and unprecedented high-resolution imaging that allows readers to zoom in to see the artist's brushstrokes, as well as previously unpublished technical photography that unveils information hidden beneath the surface of the artwork through interactive, layered images showing X-ray, infrared, and other technical imaging. For more extended conservation research and interactive images, visit the full catalogue at www.artic.edu/digitalrenoir.